Scheduled endoscopic treatment of biliary anastomotic and nonanastomotic strictures after orthotopic liver transplantation - Zhang-Hagenlocher, Christine; Rupp, Christian; Exarchos, Xenophon; Mehrabi, Arianeb; Koschny, Ronald; Schaible, Anja; Sauer, Peter (Gastrointestinal endoscopy, 2023)
Background and Aims - Biliary strictures after liver transplantation are associated with significant morbidity and mortality. Although various endoscopic treatment strategies are available, consensus on a particular strategy is lacking. Moreover, the influence of endoscopic therapy on overall survival has not been studied. This retrospective study aimed to evaluate the impact of scheduled endoscopic dilatation of biliary strictures after orthotopic liver transplantation on therapeutic success, adverse events, and survival. - Methods - Between 2000 and 2016, patients with post-transplant anastomotic and nonanastomotic strictures were treated with balloon dilatation at defined intervals until morphologic resolution and clinical improvement. The primary clinical endpoint was overall survival, whereas secondary outcomes were technical and sustained clinical success, adverse events, treatment failure, and recurrence. - Results - Overall, 165 patients with a mean follow-up of 8 years were included; anastomotic and nonanastomotic strictures were diagnosed in 110 and 55 patients, respectively. Overall survival was significantly higher in patients with anastomotic strictures than in those with nonanastomotic strictures (median, 17.6 vs 13.9 years; log-rank: P < .05). Sustained clinical success could be achieved significantly more frequently in patients with anastomotic strictures (79.1% vs 54.5%, P < .001), and such patients showed significantly superior overall survival (19.7 vs 7.7 years; log-rank: P < .001). Sustained clinical success and the presence of nonanastomotic strictures were independently associated with better and worse outcomes (P < .05), respectively. - Conclusions - Scheduled endoscopic treatment of biliary anastomotic and nonanastomotic strictures after liver transplantation is effective and safe, with high success rates. The implementation of this strategy controls symptoms and significantly improves survival.
Online verfügbar 28 August 2022, Artikelversion 13 Dezember 2022
Gesehen am 24.03.2023